Effectiveness of Puppetry in Delivery Oral Health Education Among Preschool Children : In Ar Rayyan Integrated Smart Caliph Melaka - Mai Ting Seah; Manreenajit Kaur (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Dental caries affects 60-90% of children globally. 70% of children suffer from dental caries in Malaysia. Early childhood oral education is crucial to lifelong oral hygiene habits. Traditional educational methods may not capture the attention and interest of preschool children. Thus, puppetry can be an engaging and creative learning tool to enhance comprehension and retention of oral health messages among preschool children. We aim to inculcate oral health knowledge among preschool children. A cross-sectional study was conducted at Ar Rayyan Integrated Smart Caliph Melaka, Malaysia, among 51 preschool children aged 4 to 6 years old using the purposive sampling method. A questionnaire was used to identify the oral health knowledge score in 4 intervals (before and after on day 1, day 7, and day 14). A live puppet show was performed on day 1 after the pre-test questionnaire was completed, followed by a video recording of the puppet show played daily for the preschool children after day 1 till day 14. Results showed significant improvement of mean oral health knowledge scores of 2.71 and 3.53 (pre- and post-test) on day 1 with a p-value of <0.0015. Subsequently, the mean knowledge score was 4.00 on day 7 and 4.27 on day 14. All five knowledge areas showed sustained improvement (p<0.001) over the spaced time. This indicates promising retention of oral health messages. Puppetry proved effective in the delivery and retention of oral health knowledge of preschool children. The significant and sustained increase in mean knowledge scores highlights its potential as an innovative tool in early childhood oral health education.